Prince Caspian - Lewis, C. S. (Clive Staples), 1898-1963 (Lahore, Pakistan ILQA Publication, 2015)
A beautiful hardback edition of Prince Caspian, book four in the classic fantasy series, The Chronicles of Narnia. This edition is complete with cover and colour interior art by the original illustrator, Pauline Baynes.
Keywords: Narnia (Imaginary place) -- Good and evil -- Fantasy